Famous First Papers for the Neurointensivist - Wijdicks, Eelco F.M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
A major contribution to the literature in neurology from renowned neurointensivist Eelco F.M. Wijdicks, MD, PhD, Famous First Papers for the Neurointensivist presents and critically assesses numerous papers that have made a profound impact on the diagnosis and treatment of neurologically acute conditions. In general, there has been little historical work in acute neurologic conditions, precisely because neurology is not perceived through this perspective. Famous First Papers for the Neurointensivist addresses this problem by a scholarly treatment of early descriptions of clinical signs, syndromes and presenting the development of treatment of these acute disorders. Using a uniform and easy-to-read format, the title offers a clear reproduction of each paper$1 (Bs title page, a short historical note, and a brief discussion and its implications, and a final comment to provide perspective. Landmark clinical trials that apply to acute neurology are included, and the book also briefly discusses the birth of intensive care units. Ground-breaking and indispensable for all physicians and researchers interested in neurocritical care, Famous First Papers for the Neurointensivist is a unique, original reference, providing not only a single source for discovering the most important papers in the field but also a critical analysis of the impact of each paper on the development of neurocritical care. "Dr Wijdicks has been integral to the growth and development of neurocritical care as a specialty. He has cultivated it firsthand, serving as a contemporary of Raymond Adams, C. Miller Fisher, and Allan Ropper, all pioneers in acute neurological care. He established the neurocritical care program at the Mayo Clinic in the early 1990s and has served as the editor in chief of the journal Neurocritical Care, which was first published in 2004 after the foundation of the Neurocritical Care Society. His unique vantage point allows him to bring us a book that few others could produce, Famous First Papers for the Neurointensivist. This book is an original in the field and should be on the reading list of anyone who cares for critically ill neurologic and neurosurgical patients... Reading this book from cover to cover is highly recommended. The writing is clear and concise, and the transitions are smooth. Each essay is self-contained and allows the reader to set his or her own pace. Once completed,the book serves as a great reference book because each essay stands on its own. The photographs of the manuscripts' title pages and key tables and figures are of high quality, and a translation is provided if the original work was not in English... Dr Wijdicks has sifted through the library stacks and has emerged with a book that puts the specialty of neurocritical care into historical perspective. In order to know where you are going, you must first know where you have been. This holds especially true for neurocritical care because the specialty continues to grow and flourish." -- JAMA NEUROL/VOL 70 (NO. 4), APR 2013 WWW. JAMANEURO.COMs
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology